Galoppträning och körning med två travare - Johansson, Johanna (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2011)
The aim of this study was to evaluate whether gallop training, rather than regular drive training, is worthwhile for trotters race performance.